The Relationship between Adversity Quotient and Innovative Work Behavior in the Community E-UKM Surabaya - Nurul Savira Fauziah; Meita Santi Budiani (Universitas Negeri Makassar, 2021)
This study aims to determine the relationship between adversity quotient and innovative work behavior in MSME owners (Micro, Small, Medium Business) who are members of the Surabaya E-UKM community. The research method used in this research is quantitative method. The population used is the owner of MSMEs in the culinary field who are members of the E-UKM Community, while the sampling technique uses total sampling, so that a total of 85 samples are obtained which will be divided by 30 to take part in the tryout and the remaining 55 will be used as research subjects. The results of the data analysis test were processed using the Pearson product moment correlation technique with the help of SPSS 24 software for windows. The results of the hypothesis test show that the correlation coefficient (r=0.856) with a sig. 0.000 (Sig<0.05). Based on these results, it can be concluded that there is a significant relationship between adversity quotient and innovative work behavior. The value of the correlation coefficient (r) also states the direction of a positive relationship which means that the higher the adversity quotient, the higher the innovative work behavior of the culinary sector MSME owners in the Surabaya E-UKM community.